Ricardo Palma: the Poet of Juvenilia - La Madrid Vivar, Pablo Lenin (2022)
The aim of this article is to show that the Juvenilia collection of poems constitutes Ricardo Palma's literary beginning and that the title is a neologism created by Palma. Poetry was for Palma the impetus he needed to produce his magnificent narrative, reflected in his Peruvian Traditions. Juvenilia, as a poetic testimony of her youth, appears before her other literary productions. Romanticism is the school in which it is sustained, consequently, the subjective tone of Juvenilia is one of its characteristics, such as the use of meter and poetic language that enrich Palma's work.